Efficient but occasionally imperfect vertical transmission of gut mutualistic protists in a wood‐feeding termite. Issue 2 (17th December 2019) - Michaud, Caroline; Hervé, Vincent; Dupont, Simon; Dubreuil, Géraldine; Bézier, Annie M.; Meunier, Joël; Brune, Andreas; Dedeine, Franck
Abstract: Although mutualistic associations between animals and microbial symbionts are widespread in nature, the mechanisms that have promoted their evolutionary persistence remain poorly understood. A vertical mode of symbiont transmission (from parents to offspring) is thought to ensure partner fidelity and stabilization, although the efficiency of vertical transmission has rarely been investigated, especially in cases where hosts harbour a diverse microbial community. Here we evaluated vertical transmission rates of cellulolytic gut oxymonad and parabasalid protists in the wood‐feeding termite Reticulitermes grassei . We sequenced amplicons of the 18S rRNA gene of protists from 24 colonies of R. grassei collected in two populations. For each colony, the protist community was characterized from the gut of 14 swarming reproductives and from a pool of 10 worker guts. A total of 98 operational taxonomic units belonging to 13 species‐level taxa were found. The vertical transmission rate was estimated for each protist present in a colony based on its frequency among the reproductives. The results revealed that transmission rates were high, with an average of 0.897 (±0.164) per protist species. Overall, the protist community did not differ between reproductive sexes, suggesting that both the queen and the king could contribute to the gut microbiota of the offspring. A positive relationship between the transmission rate of protists and their prevalence within populations was also detected. However, transmission rates alone do not explain the prevalence of protists. In conclusion, these findings reveal key forces behind a conserved, multispecies mutualism, raising further questions on the roles of horizontal transfer and negative selection in shaping symbiont prevalence.